The Impact of Digital Advancements and Their Influence on Marketing, Value Chains, and Business Models - Wulan Purnamasari; C. Candraningrat Candraningrat; Niken Savitri Primasari; Zainul Wasik (PT. Mawadaku Sukses Solusindo, 2024)
Although good mastery of digital innovations can be highly advantageous in today's environment, as business models and industries are changing rapidly due to digital innovations, there are significant gaps in the literature on digital innovations. By defining terms and examining the particulars of this new field of study, we add to the body of literature. The impact of digital innovation on marketing, value chain, and business models is then covered, with particular attention paid to conflicts and marketing difficulties, value chain dynamics, and business model evolutions. We offer recommendations for more research in our conclusion.